Comparison of Twitter Use of the American Society of Anesthesiologists and the American Association of Nurse Anesthetists. Issue 6 (15th September 2019) - Chu, Benjamin; Lozada, M. James; McCrory, Emery Harris; Toledo, Paloma; Antalek, Matthew; Morely, Derek; Lange, Elizabeth M. S.
Abstract : Twitter has become a powerful tool for dissemination of information. The objective of this study was to evaluate Twitter usage of the American Society of Anesthesiologists (ASA) and the American Association of Nurse Anesthetists (AANA). All tweets from ASA ("@ASALifeline") and AANA ("@aanawebupdates") were collected over a 1-year time period. The content of each tweet was categorized using a rubric. ASA generated more original tweets than AANA. Twitter use was highest in October for ASA and September for AANA. Both societies are actively using Twitter. Future work should evaluate the impact of societal Twitter use.